Kecerdasan Kultural Siswa Muslim dan Non-Muslim Di Kota Curup: Sebuah Eksplorasi Kualitatif - Hendra Harmi (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Cultural intelligence for high school students becomes important along with the many attitudes and behaviors of a person who are destructive and growing among students such as being against differences both in terms of culture, religion, language and ethnicity. Even though Indonesia as a nation and country has a uniqueness, diversity from various aspects. Therefore, for the younger generation, especially high school students, intelligence in social interaction is needed in the midst of high levels of difference, this is done as a way to minimize discrimination or anti-diversity attitudes. High cultural intelligence possessed by students in schools is expected to be able to improve harmony amid cultural differences. This article intends to explore the cultural intelligence of high school students in Rejang Lebong Regency from the perspective of Muslim and non-Muslim students.